Modifikasi perilaku peningkatan kemampuan memakai kaus pada anak dengan intellectual dissability tingkat sedang - Nafisa Alif Amalia; Luh Surini Yulia Savitri (Cognicia, 2019)
Self-help skills are an important ability to support daily life activities. One of the skills is self-dressing, especially for children which entering puberty. Yet, children with intellectual disability have difficulties in conducting self-help skills. A child with intellectual disability, especially children with moderate-severe intellectual disability, needs support in almost everyday. Eventhough, we have to teaching them to be independent and improves their quality of life. The subject for this research was a boy aged 10 years who were diagnosed with moderate intellectual disability. The purpose is to improve the ability of wearing sleeves independently. The method is single AB design. Technique used is backward chaining, prompting, and positive reinforcement. This research was conducted in 9 sessions, each having 5 trials. The results of this research is behavior modification program of wearing sleeves independently using backward chaining techniques can improve the ability of self-dressing in children with intellectual disability.